Respuesta inmune y vacunas contra la rinotraqueitis Infeccionsa bovina (1996)
ABSTRACT: Immunosupressor agent which is implicated in "shipping fever syndrome" and is associated with a decrease antibacterial activities of macrophages and polimorphonuclears neutrophyls. As well as for its ability to produce lisis of activated T lymphocytes. Since the 60's vaccines have been used against IBR, however it has not been possible to design an effective and safe product. Nowadays, some molecular technics such as clonation and genetic expression systems have permit the development of new alternatives for immunization against IBR. This article reviews the most relevant aspects of specific and nonspecific response against BHB-1, the mechanisms of immunosuppression and the expected goals in the development of a new vaccines.